River Environment Preservation Movement for the Sustainability of Ecotourism Programs - Fajar Fajar; Dewi Liesnoor Setyowati; Thriwaty Arsal; Ani Rosilawati (International Conference on Science, Education, and Technology, 2023)
The concrete action of preserving the river environment by a number of youths in Mayangsari Village has yielded results. The potential of the river has been exploited and provides economic benefits. The river which was originally a garbage dump has now been cleaned and has become a new tourist attraction. Now many visitors are coming to walk along and enjoy the flow of the Kreo river. The success of the youth in changing the face of the river is interesting to study. This article aims to identify and analyze the youth movement in preserving the river environment. This study uses a descriptive qualitative research method in studying the youth movement in river conservation. This research took place in the riverside community of Kampung Mayangsari, Kalipancur Village, Semarang City. This location was chosen because the river that flows in the city of Semarang has received serious attention from a number of concerned youths. The chairman and members of the River Care Group, the River Tubing Mayangsari Tourism Awareness Group (Pokdarwis), and the surrounding community were informants who provided primary data. Primary data is obtained by using interviews, and observations, while secondary data is taken from journal articles and documents. Analysis and interpretation of data using interactive analysis from Miles and Huberman. Youth are agents of change who take roles and responsibilities in efforts to improve social, economic, and environmental life. A number of young people who are members of the River Care Group and Pokdarwis in Kampung Mayangsari are carrying out conservation efforts in the Kreo River environment. Rivers that were previously used for the benefit of individuals who degrade river have been changed through various concrete actions in the form of cleaning rivers, making regulations and education on river protection, creating tourism infrastructure, and finally making rivers for river tubing tourism destinations that provide economic benefits for the community.